2020
DOI: 10.21203/rs.3.rs-91553/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hospital Service Quality Based on HEALTHQUAL Model and Trusting Nurses at Iranian University and Non-University Hospitals: A Comparative Study

Abstract: Background: Establishment and improvement of patients’ trust in healthcare organizations like hospitals necessitate delivering high-quality services by nurses, as the largest group of healthcare providers. The present study aimed to compare hospital service quality based on the HEALTHQUAL model and trusting nurses at university and non-university hospitals in Iran.Methods: This comparative cross-sectional study was conducted on 990 patients admitted to university and non-university hospitals located in Bushehr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
(23 reference statements)
1
5
0
Order By: Relevance
“…This result was in consistent with Nemati et al study. This study showed that patients at hospitals paid more attention to "environment" dimension based on HEALTHQUAL model [20]. Since Tangibility dimension in SERVQUAL refers to physical and observable services same as the Environment dimension in HEALTHQUAL, it can be approved that the two questionnaires present had almost similar results in terms of service users' expectations.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…This result was in consistent with Nemati et al study. This study showed that patients at hospitals paid more attention to "environment" dimension based on HEALTHQUAL model [20]. Since Tangibility dimension in SERVQUAL refers to physical and observable services same as the Environment dimension in HEALTHQUAL, it can be approved that the two questionnaires present had almost similar results in terms of service users' expectations.…”
Section: Discussionmentioning
confidence: 70%
“…Mosadeghrad and Sokhanvar revealed that the quality gaps in the provided health-care services were (− 0.57) and (− 0.58), respectively in two studies conducted based on HEALTHQUAL model [21]. Nemati et al, in a study aimed to compare the Iranian university and non-university hospitals service quality based on the HEALTHQUAL model, found that the quality gap was − 0.42 and − 0.64 for university and nonuniversity hospitals respectively [20]. The quality gap reported in these studies was less than the value mentioned in the present study, and this can be attributed to the difference between the population and study setting (hospital vs. health centers).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations